Prognostic impact of the ratio of the main pulmonary artery to that of the aorta on chest computed tomography in patients with idiopathic pulmonary fibrosis - Choi, Ji Soo (BMC Pulm Med, 2019)
BACKGROUND: In many clinical disorders, there is a relationship between the ratio of the diameter of the main pulmonary artery (mPA) to that of the aorta (Ao) on chest computed tomography (CT). The aim of this study was to determine if the mPA/Ao ratio at diagnosis is associated with the clinical characteristics and outcomes in patients with idiopathic pulmonary fibrosis (IPF). METHODS: We retrospectively reviewed the diameters of the pulmonary artery and aorta on chest CT, clinical characteristics, and results of other examinations in 303 patients at the time of initial diagnosis of IPF at our tertiary care center between 2011 and 2015. The primary outcomes were death and lung transplantation. The patients were followed up until June 2017. RESULTS: One hundred and eight patients (35.6%) died and 58 (19.1%) underwent lung transplantation during follow-up. The mean mPA and Ao diameters were 28.3 mm and 34.0 mm, respectively, and the mean mPA/Ao ratio was 0.84. Thirty-one patients (10.2%) had an mPA/Ao ratio > 1.0 and 182 (60.1%) had an mPA/Ao ratio > 0.8. Patients with an mPA/Ao ratio > 0.8 had a lower DLco value than those with an mPA/Ao ratio ≤ 0.8. In Kaplan-Meier analysis, patients with an mPA/Ao ratio > 1.0 or > 0.8 had worse outcomes than those with an mPA/Ao ratio ≤ 1.0 and ≤ 0.8, respectively. CONCLUSIONS: A higher mPA/Ao ratio based on 1.0 and 0.8 is associated with unfavorable prognosis in patients with IPF.